Influence of Urea-Dairy Cattle Dung Fertilizer Combinations on Growth and Production of Mulato Grass (Brachiaria Hybrid cv "Mulato") - Hendarto, Eko; Suwarno, Suwarno; Sudiarto, Pramono (ANIMAL PRODUCTION, 2018)
A research with the aim of obtaining an effective combination pattern of fertilization management was done on mulato grass plants (Brachiaria Hybrid cv "Mulato"). The used fertilizers were of cow dung that serves to maintain the quality of soil and urea that is useful to increase the growth and production of plants. The method used was Completely Randomized Design where the treatments were mixed dairy cattle dung at 10, 17 and 24 tons per hectare per defoliation and urea fertilizer at doses of 75, 150 and 225 kg per hectare per defoliation. Each treatment was repeated 3 times so that there were 27 plots of research. The parameters studied were plant height, tiller number, leaf number, weed population and fresh forage production. The collected data were analyzed based on Completely Randomized Design, between Orthogonal tested treatment and regression analyzed dose. The results showed that the combined treatment of cow dung as much as 24 tons per hectare per defoliation with urea of 225 kg per hectare per defoliation (K3U3) showed the best growth and production of Mulato grass, while for the given dosage yielded a linear regression equation